Approach Pattern to The Effectiveness of Local Government Policies In Reducing The Prevalence of Stunting in Central Mamberamo District Based on The Theory of Betty Neuman Study Phenomenology - Saria Dewi Sartika Hutagao; Blacius Dedi; M. Jamaluddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Poverty in Central Mamberamo Regency is exacerbated by the low daily malnutrition rate (PoU) per capita, which is only 26.1% of the AKG in 2023. This region is of particular concern because it contributed 35.42% of the highest stunting prevalence among 28 other regions in Papua in the same year. The Neuman System Model encourages the role of nurses in maintaining the stability of the client system (individual, family, group, or community) through primary, secondary, and tertiary interventions. This study aims to explore the pattern of approaches to the effectiveness of local government policies and the supporting factors and obstacles to the success of programs in reducing stunting rates in Central Mamberamo Regency based on Betty Neuman's theory. This study used a qualitative approach with a case study or applied phenomenology method, focusing on an in-depth understanding of the experiences and perspectives of various stakeholders (pregnant women, postpartum women, mothers with stunted toddlers, nurses, and heads of agencies) selected through a combination of purposive sampling and snowball sampling methods at the Kobakma Community Health Center in Central Mamberamo from June to July 2025, with sample size determined based on data saturation. The results showed that the success of the ANC program in Central Mamberamo was evident in the increase in pregnant women's weight and normal births. This is supported by Betty Neuman's theoretical approach with structured interventions (education, supplements) to prevent stunting, along with cross-sector collaboration. However, this is hampered by a shortage of professional health human resources. Government strategies, which include nutrition education, iron supplementation, and nutritional rehabilitation for stunted toddlers, have shown effectiveness in improving maternal and infant health, although human resource challenges need to be addressed urgently. This study highlights the program's success in improving ANC adherence among pregnant women and healthy birth outcomes, with cross-sector collaboration as a key contributing factor. However, inadequate human resources (HR) for health professionals was identified as an urgent inhibiting factor that needs to be addressed. Keywords: Betty neuman's theory; Policy effectiveness; Central mamberamo; Prevalence of stunting